Antigenic competition in the generation of multi-virus-specific cell lines for immunotherapy of human cytomegalovirus, polyomavirus BK, Epstein-Barr virus and adenovirus infection in haematopoietic stem cell transplant recipients - Roubalová, Kateřina; Němečková, Šárka; Kryštofová, Jitka; Hainz, Petr; Pumannová, Markéta; Hamšíková, Eva (Immunology letters, 2020)
Adoptive transfer of multivirus-specific T cell lines (MVST) is an advanced tool for immunotherapy of virus infections after hematopoietic stem cell transplantation (HSCT). Their preparation includes activation of donor virus-specific T cells by the mixture of oligopeptides derived from immunodominant antigens of several most harmful viruses, i.e. human cytomegalovirus (HCMV), polyomavirus BK (BKV), Epstein-Barr virus (EBV) and adenovirus (ADV). The aim of our study was to find out whether antigenic competition may have an impact on the expansion of virus-specific T cells. MVST from several heathy blood donors were generated using a pulse of overlapping oligopeptides (PepMixes™, derived from the IE1 and pp65 CMV antigens, VP1 and LTAG BKV antigens, BZLF1 and EBNA1 proteins of EBV and hexon protein from ADV) and short time culture in the presence of IL-7 and IL-4. The amount of virus-specific T cells in MVST was measured by ELISPOT and flow cytometry after re-stimulation with individual antigens. To evaluate antigenic competition, MVST were expanded either with a complete set of antigens or with the mixture lacking some of them. MVST expanded with the antigen mixture including CMV antigens contained a lower proportion of the T cells of other antigen specificities. A similar inhibitory effect was not apparent for EBV-derived peptides. The competitive effect of CMV antigens was most pronounced in MVST from CMV-seropositive donors and was mediated by both IE1 and pp65-derived peptides. Antigenic competition did not influence the phenotype of either CMV- or BKV-specific T cells. Both T cell populations had an effector memory phenotype (CD45RO+, CD27-, CCR7-). However, CMV-specific T cells preferentially consist of CD8+ while in BKV-specific T cells, the CD4+ phenotype predominated. Modification of the MVST manufacture protocol to prevent antigenic competition may increase the efficacy of MVST in therapy of BKV infections in HSCT recipients.
Keywords: Polyomavirus Infections; virus BK; Host-Pathogen Interactions; fenotyp; Adenovirus Infections, Human; Phenotype; Adenoviridae; Cytomegalovirus Infections; Virus Diseases; Polyomavirus BK; Epstein-Barr Virus Infections; Immunotherapy, Adoptive; virové nemoci; Antigenic competition; Herpesvirus 4, Human; virus Epsteinův-Barrové; BK Virus; Lymphocyte Activation; Tumor Virus Infections; infekce virem Epsteina-Barrové; antigeny virové; transplantace hematopoetických kmenových buněk; imunodominantní epitopy; T cell phenotype; aktivace lymfocytů; T-lymfocyty; cytomegalovirové infekce; Multi-virus-specific T cell lines; Antigens, Viral; kultivované buňky; lidé; polyomavirové infekce; infekce onkogenními viry; interakce hostitele a patogenu; Humans; adenovirové infekce lidí; imunoterapie adoptivní; Cytomegalovirus; Cells, Cultured; T-Lymphocytes; Epstein-Barr virus; Immunodominant Epitopes; Hematopoietic Stem Cell Transplantation